Case Report: Newly discovered ELN gene mutation in congenital heart disease: case analysis and review - Cheng, Peiwen; Wang, Guozhen; Qiu, Jialin; Xie, Xia; An, Yong (Frontiers in Pediatrics, 2026)
IntroductionSupravalvular aortic stenosis (SVAS) is a rare left ventricular outflow tract obstruction, most commonly caused by pathogenic variants in ELN. Truncating variants in exons 1–29 typically produce non-syndromic SVAS through elastin haploinsufficiency, whereas C-terminal variants are linked to autosomal dominant cutis laxa. However, clinically and mechanistically well-characterized variants in the distal part of this “stenotic zone,” such as exon 28, remain uncommon.MethodsWe conducted a retrospective family-based case report with standardized clinical evaluation, serial echocardiography, and trio whole-exome sequencing with Sanger confirmation and conservation analysis.ResultsA female infant presented at 1 month with severe sinotubular junction narrowing (Z-score −4.8, peak gradient 24 mmHg), severe peripheral pulmonary artery stenosis, a small atrial septal defect, and moderate mitral regurgitation. Her father had severe SVAS with mild PPAS and prior aortic root enlargement, without syndromic features. Trio sequencing identified a novel heterozygous ELN exon 28 frameshift variant, c.1879_1883dup (p.Ala629LeufsTer15), inherited from the father. Ala629 is fully conserved, and the duplication introduces a premature stop codon, consistent with nonsense-mediated decay and elastin haploinsufficiency. At 9 months, SVAS progressed (peak gradient 35 mmHg), while PPAS gradients regressed by >40%.ConclusionThis novel exon 28 ELN frameshift expands the non-syndromic SVAS spectrum and illustrates a characteristic pattern of progressive aortic stenosis with improving PPAS, supporting ELN testing and targeted longitudinal surveillance in similar patients and families.